2015
DOI: 10.1149/2.0611509jes
|View full text |Cite
|
Sign up to set email alerts
|

Semiconductivity Conversion of Passive Films on Alloy 800 in Chloride Solutions Containing Various Concentrations of Thiosulfate

Abstract: Semiconductive properties of the passive films formed on Alloy 800 in 0.1 M chloride solutions containing various concentrations of thiosulfate are investigated using Mott-Schottky analysis. The results indicate that when the concentration of the thiosulfate ions increases, the semiconductivity is converted from the n-type to the p-type. This conversion is postulated to be due to the incorporation of sulfur into the passive film, which changes the vacancy type. The breakdown behavior of the passive films is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 17 publications
0
27
0
Order By: Relevance
“…As a result, the passive film cannot be broken down in this situation. In our previous work, 39 we found that there is not pits formed on UNS N08800 surface after the polarization curve conducted in solution containing 0.1 mol · L −1 + 0.5 mol · L −1 S 2 O 3 2− . 39 The experimental observation verified that there is no pitting corrosion occurred if the chloride/thiosulfate concentration ratio is very low.…”
Section: Chloride-to-thiosulfate Concentration Ratio (Ctcr)-ctcr Ismentioning
confidence: 76%
“…As a result, the passive film cannot be broken down in this situation. In our previous work, 39 we found that there is not pits formed on UNS N08800 surface after the polarization curve conducted in solution containing 0.1 mol · L −1 + 0.5 mol · L −1 S 2 O 3 2− . 39 The experimental observation verified that there is no pitting corrosion occurred if the chloride/thiosulfate concentration ratio is very low.…”
Section: Chloride-to-thiosulfate Concentration Ratio (Ctcr)-ctcr Ismentioning
confidence: 76%
“…Therefore, no pits are initiated at a lower chloride-tothiosulfate concentration ratio [12,21]. The concentration of these two ions could affect the semiconductivity of passive film formed on alloy 800, and the semiconductivity type changes from n-type to p-type as the concentration ratio decreased, which was due to sulfur incorporation into oxygen vacancies [21].…”
Section: Methodsmentioning
confidence: 99%
“…For example, Cui et al [9] used scanning reference electrode to measure the surface potential distribution. Zhu et al [10,11] and Xia et al [12,13] used scanning electrochemical microscope (SECM) to obtain the surface reactivity of alloy 800 in chloride and thiosulfate solutions. Zhao et al [14] used Scanning Kelvin Probe (SKP) to study the potential distribution of a crack on 304 stainless steel.…”
Section: Introductionmentioning
confidence: 99%
“…S 2 O 3 2¹ can also affect the materials used in the nuclear industry. [20][21][22][23][24][25][26] Wang et al 27 found that the passive range and pitting corrosion potential of Alloy 800 in the solution containing both thiosulfate and chloride ions are lower than that in thiosulfate-only or chloride-only solutions or the sulfate + chloride ions. Z. Fang and R. W. Staehle investigated surfaces of Alloys 600, 690 and 800 after polarization over the potential range and found intergranular (IG) corrosion occurred mainly in a solution of SO 4 2¹ , sulfite (SO 3 2¹ ), tetrathionate (S 4 O 6 2¹ ), and S 2 O 3 2¹ , while S 2¹ or HS ¹ were found to produce pitting.…”
Section: ¹mentioning
confidence: 99%